NK Cells during Dengue Disease and Their Recognition of Dengue Virus-Infected cells - Beltrán, Davis; López-Vergès, Sandra (Frontiers in Immunology, 2014)
The innate immune response, in addition to the B and T cell response, plays a role in protection against dengue virus (DENV) infection and the degree of disease severity. Early activation of NK cells and type-I interferon-dependent immunity may be important in limiting viral replication during the early stages of DENV infection and thus reducing subsequent pathogenesis. NK cells may also produce cytokines that reduce inflammation and tissue injury. On the other hand, NK cells are also capable of inducing liver injury at early-time points of DENV infection. In vitro, NK cells can kill antibody-coated DENV-infected cells through antibody-dependent cell-mediated cytotoxicity (ADCC). In additional, NK cells may directly recognize DENV-infected cells through their activating receptors, although the increase in HLA class I expression may allow infected cells to escape the NK response. Recently, genome-wide association studies (GWAS) have shown an association between MICB and MICA, which encode ligands of the activating NK receptor NKG2D, and dengue disease outcome. This review focuses on recognition of DENV-infected cells by NK cells and on the regulation of expression of NK cell ligands by DENV.